PICTURES IN COLLABORATIVE LEARNING TO IMPROVE READING COMPREHENSION - Fitriyeni, Fitriyeni; Widyastuti, Tri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research aims to improve the students’ reading comprehension using pictures in Collaborative Learning. The method used is descriptive quantitative. The data is taken from the results of pretest and post test to seventh grade students of SMP 267 Jakarta. Both the average results of pretest and post test and the statistical analysis using SPSS 17 shows that there is a significant improvement of the use of pictures in Collaborative Learning. Pictures as the media of teaching stimulates the students interest and also motivate them to read more; they become familiar with the expected reading text by relating it with the pictures and their previous knowledge. To get more better result, the Collaborative Learning as the teaching method is applicated to sharpen the students’ collaboration in group learning, so they can share ideas and opinions to solve the problems they get in understanding and comprehending the reading text.